Visions of Italy [videorecording (DVD)] - Butera, Bernardo; Barchiesi, Franca; Toperoff, Sam; Brygider, Roman (WLIW Productions, 2002)
A visual itinerary, an emotional visit to a family's homeland, a souvenir of the trip of a lifetime, or the virtual realization of a fantasy vacation - whatever the inspiration, one thing's certain - locations like this can't be seen any other way.